Piloting an open-source Transport Justice Tool for Southern Africa - Pillay, Pravanya (Department of Civil Engineering, 2024)
Traditional transport planning methods largely promote transport-related social exclusion in favour of existing travel patterns. The monetary valuation of travel time savings (biased towards projects that serve higher income earners), thus generates more overall benefits and focus of alleviating network congestion. Typically, the general distributive principle of goods is equality; however, this can't easily be extrapolated in the context of transportation. Accessibility, in the transport context, can be defined as how well the transport network connects people with activities. Mobility refers to the variety of transportation options and how well they provide access to transit-connected opportunities and services. Mobility and accessibility are jointly crucial to enabling everyone to enter the economy and live better. Transport Justice, a term coined by Karel Martens (2017), develops a new paradigm for transportation planning based on principles of justice focusing on marginalised and poorer communities or groups of people. It is based on social justice philosophies centred on the concept of equality of resources. To enhance the process of regional transport planning, these principles of justice can be applied to and quantified in the evaluation of urban transportation systems. This method challenges transportation experts to conduct systematic studies of the degree of accessibility and mobility experienced by various demographic groups rather than continuing to concentrate narrowly on specific aspects of the greater transportation system. The objective of this study was to determine to what extent and how the approach and underlying analytical methods can be applied by developing an open-source analytical tool for transport planning based on principles of transport justice (mobility and accessibility). The research intended to firstly, review a suitable open-source software to determine if it could be the platform of choice for developing a robust, scalable and easy to use transport justice analysis toolkit for southern Africa; and then apply/case-test the chosen software in the cities of Kigali, Rwanda and Nairobi, Kenya. This research formed part of a larger Volvo Research and Educational Foundations (VREF) project that the University of Cape Town was involved in regarding transport planning based on the principles of justice in Africa (piloting a proof of concept in Kigali and Blantyre Malawi). The open-source analytical tool developed in this study (using r5r) showed true potential, robustness and replicability to be able to compute all the relevant and potential statistics and parameters as required to evaluate the transport justice indicators of any region. Thus, the r5r model demonstrated the robustness and scalability of the code underlying the transport justice analysis tool in this study with minimal input data set requirements.